The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/ptr.5542
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition ofHelicobacter pyloriand Its Associate Urease by Labdane Diterpenoids Isolated fromAndrographis paniculata

Abstract: The present study was carried out to evaluate anti-Helicobacter pylori and its associated urease activity of labdane diterpenoids isolated from Andrographis paniculata. A molecular docking analysis was performed by using ArgusLab 4.0.1 software. The results obtained indicate that compound A possesses strong inhibition to H. pylori, 28 ± 2.98 (minimum inhibitory concentration, 9 µg/mL), and its urease, 85.54 ± 2.62% (IC50 , 20.2 µg/mL). Compounds B, C, and D also showed moderate inhibition to H. pylori and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…However, luteolin, apigenin, diosmetin, O 4Ꞌ , O 7 ‐dihexyl apigenin, and chrysin exhibited significant inhibition toward urease compared with all other flavonoids. Several bioactive phenolic compounds were studied which were exhibiting a significant inhibitory effect and which have been identified from plant materials, among them are flavonoids, tannins, terpenes, aromatic aldehydes, alcohols, tannins, and catechins that are studied widely . Thus, the results are in accordance with reported studies.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…However, luteolin, apigenin, diosmetin, O 4Ꞌ , O 7 ‐dihexyl apigenin, and chrysin exhibited significant inhibition toward urease compared with all other flavonoids. Several bioactive phenolic compounds were studied which were exhibiting a significant inhibitory effect and which have been identified from plant materials, among them are flavonoids, tannins, terpenes, aromatic aldehydes, alcohols, tannins, and catechins that are studied widely . Thus, the results are in accordance with reported studies.…”
Section: Resultssupporting
confidence: 84%
“…Several bioactive phenolic compounds were studied which were exhibiting a significant inhibitory effect and which have been identified from plant materials, among them are flavonoids, tannins, terpenes, aromatic aldehydes, alcohols, tannins, and catechins that are studied widely. [35] Thus, the results are in accordance with reported studies. The literature reported that flavonoids showed significant urease activity, and our results are in close agreement with the literature data.…”
Section: Urease Inhibitionsupporting
confidence: 92%
“…In vitro studies found that several components from medicinal plants inhibited the activity of H. pylori urease, such as both methanol and acetone extracts from Acacia nilotica and Calotropis procera (Amin, Anwar, Naz, Mehmood, & Saari, 2013), betulinic acid and oleanolic acid from Forsythia suspense (Shin, Park, Baek, Chung, & Park, 2009), water extract from Terminalia chebula (inhibitory concentrations: 1 to 2.5 mg/mL; Malekzadeh, Ehsanifar, Shahamat, Levin, & Colwell, 2001). Labdane diterpenoids isolated from Andrographis paniculata inhibited urease activity in vitro with 50% inhibitory concentration (IC 50 ) of 20.2 μg/mL (Shaikh et al, 2016), and for dichloromethane extract from Parthenium hysterophorus roots, the IC 50 is 136.4 μg/mL (Espinosa-Rivero, Rendon-Huerta, & Romero, 2015). Pterocarpus santalinus could inhibit the activity of urease, and decrease the lipid peroxidation and lactate dehydrogenase when co-cultivated with gastric epithelial cells of rats (Narayan, Veeraraghavan, & Devi, 2007).…”
Section: Anti-urease Activitymentioning
confidence: 99%
“…214 Andrographolide sodium bisulphite showed inhibitory potency on helicobacter pylori and helicobacter pylori urease. 215,216 Andrographolide was found to suppress the expression of E-selectin at the mRNA level, reducing the adherence of gastric cancer cells to human vascular endothelial cells. 200 Treatment with andrographolide decreased proliferation and increased apoptosis in three gastric cell lines: BGC-822, SGC7901, and C666-1 depending on time and concentration.…”
Section: Gastric Cancermentioning
confidence: 98%